2019
DOI: 10.1007/s00382-018-04604-0
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing reanalysis data for understanding rainfall climatology and variability over Central Equatorial Africa

Abstract: Understanding the rainfall climatology and variability over Central Equatorial Africa (CEA) has largely been hampered by the lack of adequate in situ observations and meteorological stations for the last three decades. Large differences and uncertainties among several observational and reanalysis data sets and various climate model simulations present another big challenge. This study comprehensively assesses the currently widely used reanalysis products based on quality-controlled radiosonde observations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 56 publications
5
65
0
Order By: Relevance
“…On spatial characteristics, all reanalysis datasets, except ERA-Interim, capture the wetting trend in the Sahel, though generally over-or underestimating its magnitude. Other local trend patterns do not reflect the observational datasets and show large differences amongst reanalyses, in line with subregional studies in Ghana [21], and southern West Africa [62]. This highlights even larger uncertainties in reanalysis rainfall trends than were previously found amongst observational datasets over Africa [16], strongly discouraging the use of reanalysis rainfall fore trend studies.…”
Section: Discussionmentioning
confidence: 58%
“…On spatial characteristics, all reanalysis datasets, except ERA-Interim, capture the wetting trend in the Sahel, though generally over-or underestimating its magnitude. Other local trend patterns do not reflect the observational datasets and show large differences amongst reanalyses, in line with subregional studies in Ghana [21], and southern West Africa [62]. This highlights even larger uncertainties in reanalysis rainfall trends than were previously found amongst observational datasets over Africa [16], strongly discouraging the use of reanalysis rainfall fore trend studies.…”
Section: Discussionmentioning
confidence: 58%
“…This supports previous findings of Congo westerlies occurring throughout the year and being most developed in July–September (Nicholson & Grist, ). And the Congo Basin as a moisture source is much more likely in SON than MAM (Hua et al, ). Differences in circulation between wet days and dry days produced 850‐hPa westerly anomalies for all seasons, with the possible exception of boreal winter in northwestern Uganda (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Diem et al () examined western Uganda as a whole but did not examine changes in rainy and dry seasons. In addition, western Uganda has been included—often as a small part of a domain—in rainfall and circulation studies with diverse geographic scales; examples include Kenya and Uganda (Ongoma et al, ; Otieno & Anyah, ), eastern Africa (Nicholson, ), EEA (Gitau et al, ); the Greater Horn of Africa (Nicholson, ; Williams et al, ), and CEA or Congo Basin (Creese et al, ; Creese & Washington, ; Dezfuli & Nicholson, ; Hua et al, , ; Nicholson & Dezfuli, ). Not only is it not known how rainy‐season rainfall characteristics have changed over time within western Uganda, but it also is not known what atmospheric conditions lead to wet days and dry days within the rainy and dry seasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose MERRA reanalysis since the analyses have been performed near the A-Train constellation track. Although large spread is found in the performance among different reanalysis products over the Congo basin (Cook & Vizy, 2016), Hua et al (2019) found out that MERRA2, when compared with all other major reanalysis data sets, is the best reanalysis product that reproduces the mean climatology and interannual variability over the Congo basin. They have also found out that MERRA2 data also have the smallest biases and root-mean-square error in describing the wind fields in the lower to middle-troposphere, thus making it suitable for our meteorological analysis.…”
Section: Merra2mentioning
confidence: 95%